2019
DOI: 10.1016/j.agee.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Livestock grazing impacts on plateau pika (Ochotona curzoniae) vary by species identity

Abstract: Livestock and small burrowing mammals are potential ecosystem engineers and major drivers of ecosystem processes. Small mammals, often considered competitors with livestock, have been reported to increase in recent years and have been identified for their negative impacts on ecosystem services such as plant production and soil carbon sequestration.However, these increases and impacts by small mammals have rarely been studied with respect to how they may be influenced by livestock grazing. Here we experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…However, grazing by one or more herds may enhance the multifunctionality and multidiversity in grassland ecosystems, thus causing an effect comparable to intermediate impacts (McGregor, 2010;Clement et al, 2018;. Such trend can be observed in the diversity of plant communities (Ross et al, 2016;Pakeman et al, 2019), flies (Clement et al, 2018), butterflies (Fraser et al, 2014), rodents (Evans et al, 2015;Li et al, 2019b), and birds (Fraser et al, 2014;Evans et al, 2015). This effect may have been observed only on Ambush hunters and Other hunters because, even though these guilds are known to hunt on the surface of flowers and leaves, with a higher dominance of families like Thomisidae and Salticidae than other families, they are also capable of adopting hunting strategies on the ground and other substrates, thus not relying only in one type of vegetation structure (Gomes et al, 2018;Joseph et al, 2018;Lyons et al, 2018b,c;da Silva Bomfim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, grazing by one or more herds may enhance the multifunctionality and multidiversity in grassland ecosystems, thus causing an effect comparable to intermediate impacts (McGregor, 2010;Clement et al, 2018;. Such trend can be observed in the diversity of plant communities (Ross et al, 2016;Pakeman et al, 2019), flies (Clement et al, 2018), butterflies (Fraser et al, 2014), rodents (Evans et al, 2015;Li et al, 2019b), and birds (Fraser et al, 2014;Evans et al, 2015). This effect may have been observed only on Ambush hunters and Other hunters because, even though these guilds are known to hunt on the surface of flowers and leaves, with a higher dominance of families like Thomisidae and Salticidae than other families, they are also capable of adopting hunting strategies on the ground and other substrates, thus not relying only in one type of vegetation structure (Gomes et al, 2018;Joseph et al, 2018;Lyons et al, 2018b,c;da Silva Bomfim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of livestock grazing could benefit plateau pika populations by increasing erosion and creating additional burrowing opportunities for plateau pikas [14]. Li et al also revealed that livestock grazing could increase the risk of plateau pika outbreaks, due to it reducing the vegetation height and diminishing the plateau pika predation risk [15]. Lots of previous studies demonstrated that proper plateau pika density is beneficial to the entire ecosystem [9,10], but the fragment of suitable habitat for plateau pika may cause its population to rise and accelerate rangeland degradation, because dispersal is an infrequent event for plateau pika [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is still a controversy what the role human activities play on the blast and distribution of plateau pika [4,13]. On one hand, human activities such as overgrazing may accelerate the degradation of rangeland, offering a potential suitable habitat for plateau pika [14,15], while Zhou et al revealed that the road has played some barrier effect on the genetic interaction between the plateau pikas that inhabited the two sides of the Qinghai–Tibet Highway [16]. On the other hand, chemical and biological technology has been used to reduce the population of plateau pika year by year; however, it would recover rapidly [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because high‐diversity community can provide more food resources and foraging niche differentiation for sheep and cattle (Feng, 2014), mixed grazing of sheep and cattle had no effect on plant diversity in this community, and relative abundance of forbs and grasses under mixed grazing was between that under sheep single grazing and that under cattle single grazing. In the low‐diversity community, sheep's foraging for forbs were facilitated by cattle's foraging for grasses due to the limitation of available food resources (Li et al, 2019; Liu et al, 2016); thus, mixed grazing decreased plant diversity and relative abundance of forbs and increased relative abundance of grasses.…”
Section: Discussionmentioning
confidence: 99%